2019
DOI: 10.18823/asiatefl.2019.16.1.19.294
|View full text |Cite
|
Sign up to set email alerts
|

High and Low Achievers’ Accepted Workload, Preferred Work Form, and Perceived Usefulness in Flipped Classrooms

Abstract: Recently, flipped classrooms have received increasing research interest in various disciplines (Gaughan, 2014). Although researchers have identified major psychological factors affecting the quality of the flipped classroom, these factors have not been systematically or simultaneously examined. Drawing on the questionnaire data obtained from 39 university second-language learners of different achievement profiles, this study explores the relative effects of students' accepted workload, preferred form of work (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Despite the aforementioned potential and merit, the effectiveness of flipped classroom has not been researched in the context of mixed-level foreign-language (FL) classes. Although Chen and Liu (2019) have explored the effectiveness of a flipped approach on EFL learners" perception, they did not draw on their performance data. It is yet to be empirically established whether the flipped classroom has the potency to enhance high-and low-achieving students" FL learning outcomes to the same extent; and if not, which group of FL learners (high vs. low) would benefit more from the flipped classroom instruction.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the aforementioned potential and merit, the effectiveness of flipped classroom has not been researched in the context of mixed-level foreign-language (FL) classes. Although Chen and Liu (2019) have explored the effectiveness of a flipped approach on EFL learners" perception, they did not draw on their performance data. It is yet to be empirically established whether the flipped classroom has the potency to enhance high-and low-achieving students" FL learning outcomes to the same extent; and if not, which group of FL learners (high vs. low) would benefit more from the flipped classroom instruction.…”
Section: Introductionmentioning
confidence: 99%
“…All studies in this review involved EFL/ESL students of higher education from different parts of Asia nations. For instance, a total of 16 studies were conducted in East Asia such as China (Yu & Gao, 2022;Li & Li, 2022;Zhonggen, 2019;Zhang, 2019;Teng, 2017;Liu & Zhang, 2018;Li and Qu, 2019), Japan (Leis & Brown, 2018), Taiwan (Yang et al, 2019;Shyr & Chen, 2018;Chen & Liu, 2019Wu et al, 2017;Chen Hsieh et al, 2017) and South Korea (Lee & Wallace, 2018). In Southeast Asia, two studies were reported from Indonesia (Zainuddin et al, 2019;Aprianto et al, 2020) and one study was conducted in Thailand (Santikarn & Wichadee, 2018).…”
Section: Participants Of the Studymentioning
confidence: 99%
“…A total of 10 studies were identified using a case study which was coupled with either a qualitative (Zainuddin, Habiburrahim, Muluk, & Keumala, 2019;Aprianto, Purwati, & Anam, 2020), a quantitative (Zhang, 2019;Santikarn & Wichadee, 2018), or a mixed-method approach (Bakla, 2018;Chen & Liu, 2019;Wu et al, 2017;Abdullah et al, 2021;Akayoğlu, 2021). Zainuddin et al (2019) employed a case study design and qualitatively collected data through approach online observations and semi-structured interviews.…”
Section: Review Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Flipped learning is based on the learning theory of Bloom's revised taxonomy, whereby students first obtain factual knowledge (the lower levels of cognitive activity), perhaps outside the classroom, and then focus on the application, interpretation, and evaluation (the higher levels of cognitive activity) during the class with guidance from their teachers and classmates (Teng, 2017;Yang, Yin, & Wang, 2018). In fact, flipped learning/teaching is a pedagogical approach in which the conventional notion of classroom-based learning is inverted so that students are introduced to the learning material before class, with class time then being used to deepen understanding through problem-solving activities (Chen & Liu, 2019;Shih & Huang, 2019;Wang & Qi, 2018). Previous findings on flipped learning/teaching for language instruction are prevalent in L2 acquisition, and English is the main target language that was considered.…”
Section: Review Of Literature Flipped Learningmentioning
confidence: 99%